Pengaruh Keterampilan Sosial Dan Kedisiplinan BelajarTerhadap Prestasi IPA Siswa Kelas IV MI Muhammadiyah Program Khusus Kartasura Tahun Pelajaran 2015/2016 - Resindrayanti, Anggi (2016)
This study aims to determine the effect on achievement IPA social skills, learning discipline influence on the performance of IPA, the influence of social skills and discipline to learn the science achievement of IV graders MIM PK Kartasura. The study population was the whole class IV MIM PK Kartasura consisting of 61 students. The technique of collecting data using questionnaires and documentation. Instruments tested the validity and reliability test. Data were analyzed using multiple linear regression analysis, T test, F test, the coefficient of determination, SE and SR previously undertaken prerequisite test analysis is the normality test and linearity test based on the test results of multiple linear regression equation: Y = 22.587 + 0.196 + 0,242. The results showed: 1) there is an influence on the achievement of social skills IPA IV graders MIM PK Kartasura, based on the T test 2,552> 2,002 and sig. 0.028 <0.05 relative contribution of 44% and the effective contribution of 13.2%, 2) there is an influence on the achievement of learning discipline IPA IV graders MIM PK Kartasura, based on the T test 2,705> 2,002 and sig. 0.009 <0.05 relative contribution by 56% and the effective contribution of 16.9%, 3) there is the influence of social skills and learn to achievement IPA discipline iv graders MIM PK Kartasura, based F test values of 12.465> 3.18 and sig. 0.000 <0.05. Based on the calculation of the coefficient determination showed that the influence of social skills and discipline to learn of the achievements of science contributed 30.1% while the remaining 69.9% is influenced by other variables outside variables in this study. Keywords: learning discipline, social skills, science achievement.